Quality-Based Leadership of Principal at Vocational School 2 Sragen - Romdhoni, Moh, Prof. Dr Yetty Sarjono, M.Si, Dr. Phil. Dewi Candraningrut (2013)
This study aimed to describe (1) the characteristics of the principal working relationship with the citizens of Vocational School 2 Sragen, (2) the characteristics of the principal social relations with people surrounding Vocational School 2 Sragen. It was a qualitative study using ethnographic design. This study was conducted at Vocational School 2 Sragen. Interviews were conducted to the principal, vice principal, teachers, and students. Methods for collecting data used interviews, observations, and documentation. Data analysis began with data collection, data reduction, data presentation, and conclusion. The validity of data used triangulation of sources. The finding suggested that (1) the work relationship of the principal with the school citizen was done both formally and informally. The formal work relationship included meetings, while non‐formal work relationship included casual talks, doing sport together, and eating together. This principal's work relationship was not based on power, but it was a kind of relationship that relied on the work mechanism concept and based on trust, respect and competence. The principal held the ESQ training in order to improve the spirit and discipline of each personnel in carrying out their tasks and provide exemplary. (2) Social relation of the principal with the community was realized by doing communication and involving them in such activities organized by the school. It was also done in a cooperation of maintaining the school safety, involving community in the provision and distribution of zakat fitrah and Qurban meat and performing Friday prayer together. Principal established a good social relationship with parents in the form of cooperation in an effort to improve the quality of learners. The principal also had a good social relation and work relation with the business and industry both formally and informally associated with the industrial work practice and labor recruitment.